Konsep Pembelajaran Menurut Al-Qur’an - Syukri Syukri (Ulumuna, 2011)
Abstract: All verses Quran are opened to be interpreted in various science contexts, including education. This article focuses on study at reconstructing the instructional concept of Quran. Results of this study indicate that instructional concepts own sturdy bases in al-Qur’an. A lot of verses of Quran give indication of people to learn more about thinking than memorizing. The past occurrence mirrors the instructional dynamics of human learning. The instructors are not only Allah, but also people, bird, and nature. Al-Qur’an always learns human being based on concrete media support even if the items are eschatology and theology. The instructional conception of Quran must not only use term ‘allama-yu‘allimu, but also yuwâri, yatafakkaru containing instructional elements. This reality shows that instructional concepts of Quran put more nuances of concrete-media than abstract-verbal ones.